Consequences of High Population in Teaching and Learning of Computer Courses in Kwara State College of Education, Oro - Madandola Tajudeen Niyi; Sakariyau Sherif Niyi; Salawu Omotayo; Boye Eni Tina M.O; Jimoh Ruth Olubukola; Junaidi Salat (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The study scrutinised consequences of high population in teaching and learning of computer courses in Kwara State College of Education, Oro. The population for this study consisted of one hundred and twenty students of department of Computer Science, Kwara State College of Education Oro. Female students participated more in the study than the male students. Students between age brackets of 21 – 25 years have the highest frequency of respondents. Structured questionnaire was designed and used to collect data. The data gathered in section A of the questionnaire was analysed with frequency count and bar chart. The three formulated and tested alternative hypotheses were analysed with chi square statistical tool and all the three were accepted. The study exposed the negative consequences of overpopulated class in teaching and learning of computer courses.